Gm/ID approach for low power sustaining amplifier circuit for GHz range MEMS SAW oscillator - Kamarudin, Norlizawati; Karim, Jamilah; Md Ralib, Aliza Aini (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents the design and simulation of microelectromechanical system (MEMS) based oscillator based on CMOS MEMS surface acoustic wave (SAW) resonator and regulated cascode configuration (RGC) transimpedance amplifier (TIA). The proposed TIA is designed in a standard 0.18 μm Silterra CMOS prosess via Cadence Virtuoso software. Gm/ID technique is used to achieve higher gain and low power TIA. The simulation result shows that the voltage gain of the design circuit is 35.5dB and 2.08 GHz -3dB bandwidth. The circuit consume 1.6mW power at 1.8 V supply voltage. When integrate with 1.4GHz resonator, the phase noise of this oscillator is -105.27 dBc/Hz at 1kHz and -116.03 dBc/Hz 10kHz.